Assessment of bacterial community structure and characterisation of novel bacterial species in weaver ants Oecophylla Smaragdina / Chua Kah Ooi - Chua , Kah Ooi (2021)
The Asian weaver ant, Oecophylla smaragdina has major workers that exhibit strong territorial behaviour and are aggressive predator of other arthropods. This makes them an effective biocontrol agent against many agricultural-important insect pests. Despite its importance in pest management, microbiome information of O. smaragdina is limited. In this study, the bacterial microbiome of O. smaragdina was characterized using 16S rRNA gene amplicon sequencing. Across all 12 samples, 97.8% of the sequences constituted 16 major operational taxonomic units (OTUs) that were assigned to eight bacterial families. The core bacterial microbiome was dominated by families Acetobacteraceae and Lactobacillaceae. Spatial variation attributed to predominance of Acetobacteraceae in ant samples obtained from forest area but reduced abundance in those from urban areas was observed. This suggested influences of the ant’s living environments especially in term of food resources. Notably, two Acetobacteraceae taxa were identified in every O. smaragdina colony. Subsequently, two groups of bacterial isolates were cultivated and identified as the persistent Acetobacteraceae taxa. Selected bacterial strains from each group were taxonomically studied through a polyphasic approach. Based on morphological, physiological and biochemical characterizations, bacterial strains in MALDI-TOF cluster 3 and strain F3b2T of MALDI-TOF cluster 2 exhibited discernible phenotypic features from closely related Acetobacteraceae type members. The genomes of strains Ha5T, Ta1 and Jb2 from MALDI-TOF cluster 3 and strain F3b2T were sequenced. A 16S rRNA gene-based phylogenetic and core genome-based phylogenomic analyses revealed that these strains formed two monophyletic lineages distinctive from all current Acetobacteraceae taxa. In terms of genome-relatedness, these strains showed lower than species-level thresholds average nucleotide identity (ANI), in-silico DNADNA hybridization (DDH) and average amino acid identity (AAI) values with all current Acetobacteraceae taxa. Strains Ha5T, Ta1 and Jb2 constituted a species that exhibited high phenotypic and genomic coherences and were placed in a monophyletic lineage. These strains and strain F3b2T were differentiated from current taxa of family Acetobacteraceae based on their phenotypic differences, low genome relatedness and distant placements on distinctive lineages in phylogenetic analyses. Genomic analysis revealed that these strains possessed a plasmid-borne sole rrn operon. Further analysis of these strains revealed reduced genes for motility, mobile elements, membrane transport and central metabolic pathways. However, they retained genes for basic cellular processes, biosynthesis of most essential amino acids, cofactors and vitamins as compared to closely related type members. Despite genome reduction, genomic analysis indicated capability of these strains in nutritional provision of multiple essential amino acids, cofactors and vitamins to the host O. smaragdina as bacterial symbionts. Taken together, bacterial strains Ha5T, Ta1 and Jb2 and strain F3b2T represent novel species of two novel genera in family Acetobacteraceae. The name Oecophyllibacter saccharovorans gen. nov. sp. nov. was proposed for strains Ha5T, Ta1 and Jb2 of which strain Ha5T (= DSM106907T = LMG30589T = NBRC 113643T = KCTC62952T) was selected as the type strain. On the other hand, the name Formicincola oecophyllae gen. nov. sp. nov. was proposed for strain F3b2T (= LMG30590T = DSM106908T = NBRC113640T = KCTC62951T) and it represented the type strain of this new taxon. Keywords: